Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.2355/isijinternational.41.70
|View full text |Cite
|
Sign up to set email alerts
|

The Eftects of Superheating on Texture and Microstructure of Fe-4.5wt%Si Steel Strip by Twin-roll Strip Casting.

Abstract: Fe-4.5wt%Si strips were produced using a vertical type twin-roll strip casting process. The effect of superheat on the microstructure and texture was studied through thickness direction of the as-cast strips. The heterogeneity of texture and microstructure through thickness direction of the strips was observed. In the case of superheat 20°C, Goss texture evolved between the subsurface and the middle layer and major rolling texture with minor solidification texture evolved in the center layer. In the case of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…On the one hand, it can create extremely fine solidification microstructure owing to its relatively high cooling rate. On the other hand, it can generate desired microstructure and texture in the initial as-cast sheet [9][10][11][12][13][14], which has an influence on the evolution of microstructure and texture during rolling and annealing and the final properties [15][16][17][18][19][20][21][22]. Thus, it may be a new promising low-cost and compact way to produce 6.5 wt% silicon steel sheet by means of strip casting and rolling method.…”
Section: Introductionmentioning
confidence: 96%
“…On the one hand, it can create extremely fine solidification microstructure owing to its relatively high cooling rate. On the other hand, it can generate desired microstructure and texture in the initial as-cast sheet [9][10][11][12][13][14], which has an influence on the evolution of microstructure and texture during rolling and annealing and the final properties [15][16][17][18][19][20][21][22]. Thus, it may be a new promising low-cost and compact way to produce 6.5 wt% silicon steel sheet by means of strip casting and rolling method.…”
Section: Introductionmentioning
confidence: 96%
“…Strip casting produces thin sheets directly from the melt and generates the desired texture in the as-cast state [7][8][9][10][11][12]. In the present work, an Fe-6.5 wt%Si-0.3 wt%Al as-cast sheet was produced by the twin-roll strip casting process, and followed by hot rolling, warm rolling and annealing.…”
Section: Introductionmentioning
confidence: 99%
“…This advanced and energy-efficient technology has attracted significant attention and different strip-cast steels such as low carbon steel [7][8][9][10], stainless steel [11][12][13][14][15][16] and silicon steel [17][18][19][20][21][22][23][24][25] have been studied. The previous studies [11][12][13][14][15][16][17][18][19][20][21][22][23] indicated that the strip casting had texture advantage in manufacturing stainless steel and nonoriented silicon steel, resulting in excellent formability and magnetic properties. However, the texture requirement of grain oriented silicon steel is different from the non-oriented silicon steel and the microstructure and texture of as-cast grain oriented silicon strip are undesirable compared to the conventional hot-rolled sheet [25].…”
Section: Introductionmentioning
confidence: 99%